2017
DOI: 10.30998/deiksis.v9i01.863
|View full text |Cite
|
Sign up to set email alerts
|

Writing Apprehension in the Writing Class: Indonesian EFL Learners Context

Abstract: The aims of Writing Apprehension in the Writing Class: Indonesian EFL Learners Context research is to find out the correlation between writing apprehension towards students’ writing skill. The research was located in Universitas Indraprasta PGRI Jakarta. This research was held from August 2015 to January 2016. The method of this research was quantitative approach using survey method. The analysis of the data used Pearson Product Moment Correlation. The population was the students of Unindra who took writing su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
1
8
1
Order By: Relevance
“…The results of this study are supported by several other research studies in ESL/EFL contexts (Aljafen, 2013; Alluhaybi, 2014; Alnufaie & Grenfell, 2013; Friesen, 1990; Kostić-Bobanović, 2016; Pimsarn, 2013; Sundari & Febriyanti, 2017). They all found that the writing apprehension level was moderate among their participants.…”
Section: Findings and Discussionsupporting
confidence: 88%
“…The results of this study are supported by several other research studies in ESL/EFL contexts (Aljafen, 2013; Alluhaybi, 2014; Alnufaie & Grenfell, 2013; Friesen, 1990; Kostić-Bobanović, 2016; Pimsarn, 2013; Sundari & Febriyanti, 2017). They all found that the writing apprehension level was moderate among their participants.…”
Section: Findings and Discussionsupporting
confidence: 88%
“…To address the research question of the type of anxiety most respondents suffered from, the data of questionnaire were grouped into Somatic Anxiety, Cognitive Anxiety, and Avoidance Behaviour which were based on the items of the questionnaire. Somatic anxiety was indicated by items number 2,9,11,13,15,17,18,20,22, and 23 (10 items), cognitive anxiety was indicated by items number 1, 3, 5, 10, 16, 17, 19, 24, 25, and 27 (10 items), and avoidance behaviour was indicated by items 2, 4, 6, 8, 12, 14, 26 (7 items).…”
Section: A the Resultsmentioning
confidence: 99%
“…Slightly different from the two studies mentioned, the study by Sundari and Febriyanti investigated the correlation between writing apprehension and writing skill by involving 66 students. It found that writing apprehension and writing skill were not significantly correlated [18].…”
Section: Introductionmentioning
confidence: 93%
“…Despite the fact that second or foreign language WA is becoming an established field of research in the Indonesian context, this notion has largely been underresearched (Kusumaningputri, Ningsih & Wisangkono, 2018). Available literature shows common strands of researches on this topic are levels, types, and causes of Indonesian EFL students' WA (Wahyuni & Umam, 2017;Ariyanti, 2017;Kusumaningputri, Ningsih & Wisangkono, 2018), WA and its relation to other aspects of writing such as writing performance and topics of writing (Cahyono, Amelia, & Mutiaraningrum, 2016;Sundari & Febriyanti, 2017). Although these researches can shed some lights to the notion of foreign language WA in the Indonesian context, there are two rooms that need to be explored.…”
Section: Introductionmentioning
confidence: 99%